Dimensões da inovação social no semiárido cearense: o caso Agência de Desenvolvimento Econômico Local (ADEL) - Souza, Ana Clara Aparecida Alves de (2014)
This research aimed to analyze the dimensions of social innovation. It was adopted as a specific scenario, part of the semiarid region located in the state of Ceará, northeastern Brazil. It was investigated the work of the Local Economic Development Agency (Adel), an initiative that aimed to promote the development in semiarid of Ceará. As a base reference for this research, it was used the summary table of dimensions of social innovation, developed by Tardif and Harrison (2005) researchers from the Centre de Recherche sur les Innovations Sociales (CRISES), a Canadian institution that is a reference in the field of social innovation. In the literature about this topic, several concepts and classifications can be found. Due to this fact, it is possible to say that this is a concept in construction. However, the definitions here presented are relate in essence when the main subject of this kind of innovation is highlighted, specifically the improving of people’s quality of life. For the purposes of this research, it was used the definition by CRISES (2012), that says that social innovation is related to a process initiated by actors in order to respond to social needs, offering a solution or benefiting from an opportunity to change social relations, turning a scenario or proposing new cultural guidelines for improving the quality and conditions of life in the community. In order to achieve the subject of this study, we adopted qualitative research techniques grounded in the positivist philosophical conception. The nature of this study is characterized as exploratory and descriptive research and the strategy adopted was the case study. Specific methods for data and analysis collection were used: documentary research and semi-structured interviews with members of the Adel and people that were benefited by their activities. The results founded highlighted the work conducted by Adel and its major programs, focused on family farming and rural youth entrepreneurship. There were also the variables of dimensions of social innovation and other emerging from this case study, based on the summary table used as a reference. This case study of Adel highlights the importance and characteristics of social innovation in the studied context, revealing that the NGO as successful initiative and reference for other regions where also happen similar challenges.